Peer Review : SISTEM MORFOLOGI BAHASA GAYO: KAJIAN TRANSFORMASI GENERATIF* - Zainuddin . (BAHAS, 2012)
ABSTRAK This paper describes the morphological system of Gayo language (SMBG), a sub-system of grammar in the field of linguistics. It is aimed at describing the morphological phenomena of word formation rules through the process of affixation, reduplication and composition, as a major issue in this study, in terms of developing the typology of language. The theory of word formation process applied Halle’s model (1973) in generative morphology that requires four steps or sub-components, namely (1) a list of morpheme, (2) the rules of word formation, (3) filter, (4) dictionary.  This study used a descriptive qualitative method in which the analysis is primarily based on the description of the grammatical meaning of morphological process. The finding showed that the type and pattern of morphophonemic in SMBG consisting of six types of rules and two types of patterns: such as rule assimilation nasal phoneme / N- / and inhibitory phoneme / p /, with the deep and surface of the structural pattern (SA-SL). Productivity morphemes process in BG include: (1) Affix forming verbs, such as: prefix {muN-}, confix {muN-(-әn)}. (2) Affix forming nouns, such as: prefix {pәN-}, infix{-әn-}. (3) Affix forming adjectives, such as: confix {muN-(-ən)}, prefix {mu-}. (4) Affix forming reduplication such as: suffix {-ən}, prefix {mu-}. (5) affixes forming composition, such as: prefix {mu-}, confix {i-(-ən)}. The typology of BG, it tends to include in the type of mixed type in terms of formation processes at the level of affixation, reduplication, and composition. And said to be qualitative type, since within the words mostly consisting of two morphemes. like muninget, 'remember', which consists of two morphemes, namely [{mu-} + (inget)}], where mu- as bound morphemes and ingat recall (MD). Potential forms found in the BG include / pengunenen /, / penyerahen /, / penyantiren /, / murumen /, / mukamulen /, / penyantoken /, / berguruen /, / perojoken /. Among the words that have the potential exists idiosyncrasy phonological, idiosyncrasy semantic, and lexical idiosyncrasy.   Kata Kunci: Morfologi Bahasa Gayo: Kajian Transformasi Generatif